Interactive Media Based on Virtual Manipulatives for Teaching Basic Division Facts - Sintya Wulandari; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Jurnal Ilmiah Sekolah Dasar, 2025)
Math learning in inclusive classrooms often faces challenges in conveying abstract concepts to students with special needs, especially on basic division facts. Innovative learning media is needed to help students understand concepts effectively and interestingly. This research aims to analyze, evaluate, and develop learning media based on virtual manipulatives to improve students' understanding of mathematics concepts. This research uses a type of development research with the ADDIE model research design (Analysis, Design, Development, Implementation, Evaluation). The subjects in this development research consisted of 2 material experts, 2 media experts, and 9 students in the inclusion class. Data were collected using test, interview, observation, and questionnaire methods, with instruments in the form of observation sheets, expert validation sheets, and evaluation tests. Data analysis was done quantitatively and qualitatively to measure the validity, practicality, and effectiveness of the product. The results showed that the virtual manipulatives-based media was valid, practical, and effective in improving students' understanding of basic division facts. This media is able to provide learning experiences that are interactive, interesting, and in accordance with the characteristics of inclusive students. The conclusion of this study is that Virtual Manipulatives can be an innovative solution to overcome the challenges of learning mathematics in inclusive classrooms.